Application of two-stage evaluation and optimization update methods for the structural damage detection of a portal beam structure. (February 2021) - Lee, Nien-Lung
Abstract: In this study, a modal-based structural damage identification method is proposed and applied to a portal beam structure as a case study. A two-stage evaluation method, involving the combination of a residual force vector method and an eigensensitivity method, is proposed to determine the locations of damaged elements in a finite element model. The physical model variables of these elements are then updated using an optimization updating method that detects damage severity. The optimization algorithm to update the model is solved using a sequential quadratic programming method. The severity of the elemental damage is indicated by the final updated physical model variables of the finite element analysis model. The effectiveness of the two-stage evaluation and optimization update methods is verified via comparison of the reference and updated physical model variables through the case study. It is determined that the structural damage detection method with two-stage evaluation and optimization updating developed in this study could be applied for the monitoring and early warning of structural damage.